2015
DOI: 10.3389/fpls.2015.00242
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phenotypes associated with anomalous stamen development in Alternanthera philoxeroides

Abstract: Alternanthera philoxeroides is a perennial amphibious weed native to South America but has now spread to diverse parts of the world. A. philoxeroides reproduces both sexually and asexually in its native range, but propagates solely through vegetative means in its introduced range. Traits associated with sexual reproduction become degraded for sexual dysfunction, with flowers possessing either pistillate stamens or male-sterile anthers. Degradations of sexual characters for loss of sexuality commonly take place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…To reduced potential phenotypic differences among the plants due to variation in parental environments, the plants had been propagated vegetatively for 4 years in a heated greenhouse at Forest Science Co., Ltd., of Beijing Forestry University. In China and Australia, A. philoxeroides does not produce viable seeds (Sainty et al, 1998; Zhu et al, 2015). Studies using molecular markers showed that populations sampled in South China derived from a single genotype (Xu et al, 2003; Wang et al, 2005; Li and Ye, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…To reduced potential phenotypic differences among the plants due to variation in parental environments, the plants had been propagated vegetatively for 4 years in a heated greenhouse at Forest Science Co., Ltd., of Beijing Forestry University. In China and Australia, A. philoxeroides does not produce viable seeds (Sainty et al, 1998; Zhu et al, 2015). Studies using molecular markers showed that populations sampled in South China derived from a single genotype (Xu et al, 2003; Wang et al, 2005; Li and Ye, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In most of the introduced regions, it reproduces asexually, primarily from stem nodes and shoot fragments ( Julien et al, 1995 ; Geng et al, 2007 ). Despite the extremely low genetic diversity of A. philoxeroides in China ( Xu et al, 2003 ; Wang et al, 2005 ), the species experienced massive vegetative propagation and rapid expansion in China ( Xu et al, 2003 ; Ye et al, 2003 ; Wang et al, 2005 ; Zhu et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Griseb.] (Li et al 2015;Zhu et al 2015). However, a majority (88.7%) of the transcripts with no similarity to the nonredundant database still have similarity to one or more of the genome assemblies ( Supplementary File 2).…”
Section: Assessment Of the Rna-seq Assemblymentioning
confidence: 99%